Influence of Root Exudates on the Bacterial Degradation of Chlorobenzoic Acids - Blanka Vrchotová; Petra Lovecká; Milena Dražková; Martina Macková; Tomas Macek (The Scientific World Journal)
Degradation of chlorobenzoic acids (e.g., products of microbial degradation of PCB) by strains of microorganisms isolated from PCB contaminated soils was assessed. From seven bulk-soil isolates two strains unique in ability to degrade a wider range of chlorobenzoic acids than others were selected, individually and even in a complex mixture of 11 different chlorobenzoic acids. Such a feature is lacking in most tested degraders. To investigate the influence of vegetation on chlorobenzoic acids degraders, root exudates of two plant species known for supporting PCB degradation in soil were tested. While with individual chlorobenzoic acids the presence of plant exudates leads to a decrease of degradation yield, in case of a mixture of chlorobenzoic acids either a change in bacterial degradation specificity, associated with 3- and 4-chlorobenzoic acid, or an extension of the spectrum of degraded chlorobenzoic acids was observed.